The motivational predictors and gender differences of academic outcomes in upper secondary education: exploring the role of growth mindset, self-efficacy, grit and passion - Sætre, Birger Olav; Sigmundsson, Hermundur (Frontiers in Education, 2026)
This study examined how four motivational constructs—growth mindset, self-efficacy, grit, and passion for achievement—relate to school outcomes among upper secondary students in Norway. Specifically, it investigated how these constructs predict perceived competence, in-subject wellbeing, and grades in Norwegian and physical education, and whether gender is associated with differences in motivation and school-related outcomes. The sample consisted of 249 students (148 females, 99 males, 1 other and 1 did not answer), aged 15 to 19, recruited from general studies (43.8%), vocational studies (24.5%), and sports programs (31.7%). Participants completed a survey including measures of growth mindset, self-efficacy, grit, and passion for achievement. Data were analyzed using t-tests, correlational analyses, and linear regression. Growth mindset emerged as the most consistent predictor of academic outcomes across both school subjects; Norwegian, Physical education; while self-efficacy showed significant predictive effects only in physical education, specifically for perceived competence and wellbeing. Passion for achievement was consistently correlated with all outcome variables but did not demonstrate unique predictive value in regression models. Grit showed weaker and less consistent correlations but significantly predicted in-subject wellbeing in Norwegian. The study also revealed significant gender differences in favor of males in passion and grit, but this did not translate into better academic performance, as females scored better in perceived competence and grades in Norwegian. These findings highlight the importance of cognitive motivational constructs in structured academic settings and suggest that supporting students' belief in their ability to improve may be particularly impactful. The results also offer new insight into gender-based differences in motivation and educational outcomes.